PERAN PSIKOLOGI PENDIDIKAN AGAMA KRISTEN DALAM PROSES PEMBELAJARAN ANAK USIA DINI DI MASA PANDEMI - Wiwiet Arie Shanty; Talizaro Tafonao (Sekolah Tinggi Teologi Ekumene Jakarta., 2021)
The purpose of writing this article is to see the extent of the role of psychology in Christian Religious Education in preparing learning methods for early childhood during the pandemic. This is because PAUD learning during the COVID-19 pandemic is a concern and challenge for teachers in carrying out learning. In addition, education in early childhood requires an adequate strategy. For this reason, teachers are required to try to understand the various problems faced in educating early childhood. The research method used is qualitative with data collection through direct observation by researchers and interviews with teachers and parents. The analysis process is carried out using various literature sources, both journals, books, and other trusted reference materials to support the author's analysis. The results of the research conducted found that the role of Christian religious education psychology in the implementation of early childhood learning was very large because it determined the methods and strategies of early childhood learning during the pandemic, namely online and face-to-face with a purpose. Pay attention to health protocols. Educational psychology during the pandemic is very significant as a solution in understanding students' cognitive, affective, psychomotor, and spiritual needs.